Effects of acetaminophen on risk taking. Issue 7 (30th July 2020) - Keaveney, Alexis; Peters, Ellen; Way, Baldwin
Abstract: Acetaminophen, an analgesic and antipyretic available over-the-counter and used in over 600 medicines, is one of the most consumed drugs in the USA. Recent research has suggested that acetaminophen's effects extend to the blunting of negative as well as positive affect. Because affect is a determinant of risk perception and risk taking, we tested the hypothesis that acute acetaminophen consumption (1000 mg) could influence these important judgments and decisions. In three double-blind, placebo-controlled studies, healthy young adults completed a laboratory measure of risk taking (Balloon Analog Risk Task) and in Studies 1 and 2 completed self-report measures of risk perception. Across all studies (total n = 545), acetaminophen increased risk-taking behavior. On the more affectively stimulating risk perception measure used in Study 2, acetaminophen reduced self-reported perceived risk and this reduction statistically mediated increased risk-taking behavior. These results indicate that acetaminophen can increase risk taking, which may be due to reductions in risk perceptions, particularly those that are highly affect laden.